PHYSIOTHERAPY AS A PART OF A COMPLEX NON-PHARMACOLOGICAL TREATMENT OF OBESITY IN MEDICAL SPA ENVIRONMENT - Belovičová, M. (Україна. Здоров’я нації, 2023)
In European countries, medical spas belong under health care. Implementing spa treatment positively influences patients´ health, as proved by evidence from history as well as by modern scientific knowledge. The results of researches carried out by universities and research institutes also demonstrate the reasonability of treatments based on the use of natural healing resources. It is about types of treatment of both - chronic and post-acute conditions - as well as about treatment aimed at lifestyle diseases and their prevention.